A Modified Peptide Derived from Goodpasture Autoantigen Arrested and Attenuated Kidney Injuries in a Rat Model of Anti-GBM Glomerulonephritis - Shi, Yue (J Am Soc Nephrol, 2020)
BACKGROUND: In Goodpasture disease, the noncollagenous domain 1 of the α3 chain (α3NC1) of type IV collagen is the main target antigen of antibodies against glomerular basement membrane (GBM). We previously identified a nephritogenic epitope, P14 (α3(127–148)), that could induce crescentic nephritis in WKY rats, and defined its core motif. Designing a modified peptide, replacing critical pathogenic residues with nonpathogenic ones (on the basis of homologous regions in α1NC1 chain of type IV collagen, known to be nonpathogenic), might provide a therapeutic option for anti-GBM GN. METHODS: We synthesized a modified peptide, replacing a single amino acid, and injected it into α3-P14–immunized rats from day 0 (the early-treatment group) or a later-treatment group (from days 17 to 21). A scrambled peptide administrated with the same protocol served as a control. RESULTS: The modified peptide, but not the scrambled peptide, attenuated anti-GBM GN in both treatment groups, and halted further crescent formation even after disease onset. Kidneys from the modified peptide–treated rats exhibited reductions in IgG deposits, complement activation, and infiltration by T cells and macrophages. Treatment also resulted in an anti-inflammatory cytokine profile versus a proinflammatory profile for animals not receiving the modified peptide; it also reduced α3-P14–specific T cell activation, modulated T cell differentiation by decreasing Th17 cells and enhancing the ratio of Treg/Th17 cells, and inhibited binding of α3-P14 to antibodies and MHC II molecules. CONCLUSIONS: A modified peptide involving alteration of a critical motif in a nephritogenic T cell epitope alleviated anti-GBM GN in a rat model. Our findings may provide insights into an immunotherapeutic approach for autoimmune kidney disorders such as Goodpasture disease.